Comparative analysis of the performance of olympic games-2024 finalists in wrestling - Latyshev S.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to perform a comparative study of the performance traits of male and female wrestlers in the disciplines of freestyle and Greco-Roman wrestling at the Olympic Games in Paris in 2024. Methods and structure of the study. The following approaches were employed in the research: a review of scholarly and methodological publications, video analysis, and timing of the competitive matches for the first and third places in each weight class at the Paris 2024 Olympic Games in wrestling for both men and women (freestyle and Greco-Roman wrestling), as well as the application of mathematical statistical techniques. Results and conclusions. The following aspects of the competitive performance of wrestlers were calculated: the average duration of a bout, the average time spent wrestling in the standing and clinch positions separately, the intensity and consistency of wrestling in the standing position, the overall effectiveness of the bout, and the effectiveness of wrestling in the standing and clinch positions separately, as well as the number of high-scoring bouts. Subsequently, a comparative analysis of these aspects was conducted based on gender and wrestling discipline. The analysis revealed that the key indicators of entertainment and success in a wrestling match, such as activity, effectiveness, and high-scoring, were highest for male wrestlers specializing in freestyle and lowest for Greco-Roman wrestlers. The disparities in these indicators were substantial, varying from 1,29 to 2,52 times. The efficacy of grappling on the ground is significantly higher for men in two categories, with a ratio of more than two to one, and for women, it is 1,27 times more effective. This necessitates a substantial overhaul of the training regimen for athletes, with a focus on enhancing their technical and tactical abilities in the clinch, particularly for men.